Developing a core outcome set for gender-affirming healthcare in transgender and gender diverse adults in Sweden using the Delphi approach: a study protocol - Fotios C Papadopoulos; Alkistis Skalkidou; Jens Högström; Louise Frisen; Mats Holmberg; Cecilia Dhejne; Malin Indremo; Åsa Tivesten; Owe Bodlund; Lisann Dahlén; Klara Pettersson; Frank Berglund; et al. (BMJ Open)
Introduction Despite an increasing amount of research related to gender-affirming treatment (GAT) outcomes among transgender and gender-diverse (TGD) people (ie, people who experience discomfort or distress in the misalignment between their gender and sex assigned at birth) in recent years, the evidence base for current recommendations is suboptimal. One contributing factor is the heterogeneity in the outcomes and outcome measures used. This study seeks to address this challenge by developing a foundational core outcome set (COS) to be used for TGD adults receiving GAT in Sweden.Methods Recommendations from the Core Outcome Measures in Effectiveness Trials initiative will be used to address this aim in four phases. Phase 1, an umbrella review of peer-reviewed literature and international guidelines in GAT will be conducted to identify relevant outcomes. In phase 2, we will solicit input from TGD individuals through the review of patient and interest organisations’ reports and an anonymous survey to identify outcomes of personal significance. In phase 3, using the Delphi method, 2–3 rounds of assessment will be conducted where researchers, healthcare professionals, policy-makers and TGD adults rate the identified outcomes by perceived importance. In phase 4, a consensus meeting will convene representatives from all stakeholder groups to finalise the COS.Analysis The results of this study will consist of a COS for GAT regarding TGD adults in Sweden. Participant survey responses will be evaluated using interpretive analysis to identify core outcomes. During each of the Delphi rounds, Likert-type scale ratings will be aggregated for outcomes to advance or be eliminated in each round.Ethics and dissemination The study has received ethical approval by the Swedish Ethical Review Authority (Umeå medicine department, Registration number: 2024-04672-01). The results of this study will be published open-access and disseminated through TGD interest organisations and a Swedish research network for gender dysphoria.Trial registration number COMET registration number 3223.